2023
DOI: 10.1017/s0024282923000269
|View full text |Cite
|
Sign up to set email alerts
|

Punctelia borreri and P. subrudecta (Parmeliaceae) associate with a partially overlapping pool of Trebouxia gelatinosa lineages

Isaac Garrido-Benavent,
María Reyes Mora-Rodríguez,
Salvador Chiva
et al.

Abstract: An increasing number of studies are describing the diversity of lichen phycobionts, which is leading to a better understanding of how lichen communities are assembled at different taxonomic, evolutionary and geographical scales. The present study explores the identity and genetic diversity of the microalgal partners of Punctelia borreri and P. subrudecta, two tropical and temperate parmelioid lichen fungi that often grow in temperate and Mediterranean forest ecosystems in Europe. Based on a specimen sampling d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Because previous studies have shown that lichen-forming fungi tend to preferentially select photobiont lineages which are better adapted to local environmental conditions [ 18 , 19 , 20 , 21 , 22 , 23 ], we will here test the following hypotheses: (i) mycobionts in the R. farinacea group associate differentially with phycobionts in Macaronesia and Mediterranean, temperate, and Boreal regions in Europe; and (ii) the association with different phycobionts shapes the ecological distribution of the mycobionts. In doing this, we will investigate the complexity of interactions among mycobiont and phycobiont lineages, the degree of specificity across their geographic distributions [ 24 , 25 , 26 ], and the climatic niche width of the primary phycobionts.…”
Section: Introductionmentioning
confidence: 99%
“…Because previous studies have shown that lichen-forming fungi tend to preferentially select photobiont lineages which are better adapted to local environmental conditions [ 18 , 19 , 20 , 21 , 22 , 23 ], we will here test the following hypotheses: (i) mycobionts in the R. farinacea group associate differentially with phycobionts in Macaronesia and Mediterranean, temperate, and Boreal regions in Europe; and (ii) the association with different phycobionts shapes the ecological distribution of the mycobionts. In doing this, we will investigate the complexity of interactions among mycobiont and phycobiont lineages, the degree of specificity across their geographic distributions [ 24 , 25 , 26 ], and the climatic niche width of the primary phycobionts.…”
Section: Introductionmentioning
confidence: 99%